(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Individuals with cancer experience substantial distress, including anxiety and depression, due to disease burden and impending death. Aim Psycho-spiritual interventions such as logotherapy could enhance the mental health of these patients. This systematic review and meta-analysis study aimed to investigate the impacts of logotherapy on depression and anxiety in patients with cancer. Materials and methods PubMed, Proquest, Web of Science, Scopus, and Google Scholar were searched. Cochrane Collaboration’s tool was utilized for the risk of bias assessment. A random-effect model was applied to estimate the pooled effect sizes. Statistical analyses were performed using STATA software version 17. Results Twenty-five clinical trial studies were included in the systematic review. Twenty-three studies investigated the impact of logotherapy on depression and twenty studies were included to assess the effects of logotherapy on anxiety in cancer patients. The meta-analysis results showed a significant effect of logotherapy compared with routine care for anxiety (SMD: -9.38 [-17.50, -1.26], I2: 99.93%) and depression (SMD: -4.67 [-5.90, -3.44], I2: 96.29%). Other findings revealed no significant differences among the subgroups on group formation, cancer stage, and cancer type. Egger’s and Begg’s test showed potential risk of bias in studies. Conclusion This study demonstrated that logotherapy led to a significant improvement in anxiety and depression of patients with cancer. It seems that finding meaning in life could help cancer patients to deal with cancer adversities. BJMS, Vol. 25 No. 01 January’26 Page : 38-51